Telescope: An Object-Oriented Architecture for Visualization Systems - Orosco, Ricardo Fabián (1998)
The construction of information visualization systems is a difficult task. The provision of an object-oriented software architecture for this kind of systems can help to reduce this difficulty. However, this approach is not currently used in most visualization systems. In this work, Telescope, an object-oriented architecture for visualization systems, is presented. Its main goal is to facilitate this construction, taking advantage of the benefits of the object-oriented paradigm (reusability, extensibility, and maintainability). The Telescope architecture is based on six main components, which are common to all information visualization systems: data representation, data abstraction, data objects- graphical objects mapping, presentation, interaction and visualization state. CityVis, a visualization system for city data, developed using Telescope architecture is described, showing the implementation of each Telescope component. Also, the implementation of several features in visualization systems, such as visualization techniques and management of abstraction levels and revealed information is described. Finally, current work and conclusions of the project are explained.